Answer:
(5, -7)
Step-by-step explanation:
There are two ways. The first is to just look at the graph and where they converge. The second way takes some math. If you would like the math explanation, let me know. I'd be happy to provide!!
I hope this helped :)
y = x - 3
y = 7x + 3
Answer:
x=-1, y=-4
Step-by-step explanation:
For this question, you can replace y in one equation with the second one.
This means x-3=7x+3.
From there, you subtract x from each side, giving -3=6x+3.
Subtracting 3from each side makes it -6=6x.
Dividing both sides by 6 leaves x isolated, with a result of x=-1.
You can substitute the value of x into either equation to work out y. I'm using the first one, as it has smaller numbers.
This equation is now y=-1-3, which can be solved for y=-4.
**This content involves simultaneous equations, which you may wish to revise. I'm always happy to help!
Answer:
Answer:
Only "One of the factors is (x + 5)." is TRUE.
Step-by-step explanation:
Note: Putting all those 4 values into the function , whichever value makes the function equal to 0, the corresponding expression would be considered a factor of the function.
As we can see, only putting in the function gives us a value of 0. So the corresponding expression is a factor of the function.
Answer:
No.
Step-by-step explanation: